2006
DOI: 10.1002/bjs.5485
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic incisional hernia repair with a self-centring suture

Abstract: Laparoscopic incisional hernia repair using a self-centring suture provides good long-term results with low complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…[121820244448] This technique can cause chronic postoperative pain. Sutures can be used to fix the mesh in centre or periphery.…”
Section: Discussionmentioning
confidence: 99%
“…[121820244448] This technique can cause chronic postoperative pain. Sutures can be used to fix the mesh in centre or periphery.…”
Section: Discussionmentioning
confidence: 99%
“…All studies used a minimum mesh overlap of 3–5 cm. Thirty studies reported the percentage of patients at last follow‐up, with a median of 98 (range 76–100) per cent. Follow‐up was given as either a mean or median value, with an overall median of 22 (range 6–64) months.…”
Section: Resultsmentioning
confidence: 99%
“…A natural progression of this was to insert the mesh in the peritoneal cavity, as close to the defective posterior sheath as possible. Fear of mesh related intestinal complications lead to the development of intraperitoneal on lay meshes (IPOM), with anti-adhesive properties [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This method of repair gathered popularity among surgeons rapidly as a method of repairing ventral and/or incisional hernias [8]. This has been driven by the promise of supplying strength to abdominal wall, spreading tension with minimal side effects from adhesions to bowels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation